Kebijakan Wali Kelas Dalam Meningkatkan Mutu Belajar Siswa di Kelas - Ahmad Mukhlasin; Eka Putri Wildyani; Rani Zaskia Ariesky; Khoirun Isnawan; Bella Bunda (Universitas 45 Surabaya, 2024)
The aim of writing this article is to describe the homeroom Teacher’s policy in improving the quality of student learning in class. This article is scientific work created using a case study approach wth the research subject being student and teacher teaching in class. Meanwhile, The object of research is teacher policy. The data collection technique used is observation. The research results show that teacher policies have a big influence in improving the quality of student learning in the classroom.